2021
DOI: 10.21203/rs.3.rs-639947/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Value of ROX Index in Predicting the Outcome of High Flow Nasal Cannula: A Systematic Review and Meta-analysis

Abstract: Background: High flow nasal cannula (HFNC) therapy is widely employed in acute hypoxemic respiratory failure (AHRF) patients. However, the techniques for predicting HFNC outcome remain scarce.Methods: PubMed, EMBASE, and Cochrane Library were searched until April 20, 2021. We included the studies that evaluated the potential predictive value of ROX (respiratory rate-oxygenation) index for HFNC outcome. This meta-analysis determined sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…However, relevant studies suggested that ROX index can be used as a new potential marker to identify patients at high risk of HFNC failure. But its prediction effect is not good, and further research is needed to determine the best cut-off value of ROX index and to promote the acquisition time of ROX index [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, relevant studies suggested that ROX index can be used as a new potential marker to identify patients at high risk of HFNC failure. But its prediction effect is not good, and further research is needed to determine the best cut-off value of ROX index and to promote the acquisition time of ROX index [15].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical factors such as the severity of illness, demographic factors, and others have been correlated with intubation delays. Even outside the intensive care unit (ICU), the HFNC is used to treat acute hypoxemic respiratory failure (AHRF), and the ROX index may be used to predict HFNC failure (Vega et al, 2022;Junhai et al, 2021;Suliman et al, 2021;Nguyen et al, 2021). The fundamental purpose of this research is to assess the ROX index using a high-flow nasal cannula as a potential predictor of delaying intubation.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…5 Studies on predictors of HFNC therapy in pediatric population still shows inconsistent results. 9 This study aims to nd the reliability of the ROX index and modi ed P-ROX index as predictors of HFNC therapy failure in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%